DNA methylation differences at birth after conception through ART. Issue 1 (23rd November 2020) - Tobi, Elmar W; Almqvist, Catarina; Hedman, Anna; Andolf, Ellika; Holte, Jan; Olofsson, Jan I; Wramsby, Håkan; Wramsby, Margaretha; Pershagen, Göran; Heijmans, Bastiaan T; Iliadou, Anastasia N
Abstract: STUDY QUESTION: Is there a relation between ART and DNA methylation (DNAm) patterns in cord blood, including any differences between IVF and ICSI? SUMMARY ANSWER: DNAm at 19 CpGs was associated with conception via ART, with no difference found between IVF and ICSI. WHAT IS KNOWN ALREADY: Prior studies on either IVF or ICSI show conflicting outcomes, as both widespread effects on DNAm and highly localized associations have been reported. No study on both IVF and ICSI and genome-wide neonatal DNAm has been performed. STUDY DESIGN, SIZE, DURATION: This was a cross-sectional study comprising 87 infants conceived with IVF or ICSI and 70 conceived following medically unassisted conception. The requirement for inclusion in the study was an understanding of the Swedish language and exclusion was the use of donor gametes. PARTICIPANTS/MATERIALS, SETTING, METHODS: Participants were from the UppstART study, which was recruited from fertility and reproductive health clinics, and the Born into Life cohort, which is recruited from the larger LifeGene study. We measured DNAm from DNA extracted from cord blood collected at birth using a micro-array (450k array). Group differences in DNAm at individual CpG dinucleotides (CpGs) were determined using robust linear models and post-hoc Tukey's tests. MAIN RESULTS AND THE ROLE OF CHANCE: We found no association of ART conception with global methylation levels, imprinted loci and meta-stable epialleles. In contrast, we identify 19 CpGs at which DNAm was associated with being conceived via ART (effect estimates: 0.5–4.9%, P FDR < 0.05), but no difference was found between IVF and ICSI. The associated CpGs map to genes related to brain function/development or genes connected to the plethora of conditions linked to subfertility, but functional annotation did not point to any likely functional consequences. LIMITATIONS, REASONS FOR CAUTION: We measured DNAm in cord blood and not at later ages or in other tissues. Given the number of tests performed, our study power is limited and the findings need to be replicated in an independent study. WIDER IMPLICATIONS OF THE FINDINGS: We find that ART is associated with DNAm differences in cord blood when compared to non-ART samples, but these differences are limited in number and effect size and have unknown functional consequences in adult blood. We did not find indications of differences between IVF and ICSI. STUDY FUNDING/COMPETING INTEREST(S): E.W.T. was supported by a VENI grant from the Netherlands Organization for Scientific Research (91617128) and JPI-H2020 Joint Programming Initiative a Healthy Diet for a Healthy Life (JPI HDHL) under proposal number 655 (PREcisE Project) through ZonMw (529051023). Financial support was provided from the European Union's Seventh Framework Program IDEAL (259679), the Swedish Research Council (K2011-69X-21871-01-6, 2011-3060, 2015-02434 and 2018-02640) and the Strategic Research Program in Epidemiology Young Scholar Awards, Karolinska Institute (to A.N.I.) and through the Swedish Initiative for Research on Microdata in the Social And Medical Sciences (SIMSAM) framework grant no 340-2013-5867, grants provided by the Stockholm County Council (ALF-projects), the Strategic Research Program in Epidemiology at Karolinska Institutet and the Swedish Heart-Lung Foundation and Danderyd University Hospital (Stockholm, Sweden). The funders had no role in study design, data collection, analysis, decision to publish or preparation of the manuscript. The authors declare no competing interests. TRIAL REGISTRATION NUMBER: N/A.